Enhancing the interfacial stability between argyrodite sulfide-based solid electrolytes and lithium electrodes through CO2 adsorption. Issue 6 (23rd January 2023) - Jiang, Shi-Kai; Yang, Sheng-Chiang; Huang, Wei-Hsiang; Sung, Hung-Yi; Lin, Ruo-Yun; Li, Jhao-Nan; Tsai, Bo-Yang; Agnihotri, Tripti; Nikodimos, Yosef; Wang, Chia-Hsin; Lin, Shawn D.; Wang, Chun-Chieh; et al.
Abstract : The CO2 treatment on argyrodite sulfide-based solid electrolyte Li6 PS5 Cl (LPSC) can effectively improve the interfacial stability between the Li and LPSC. Abstract : Argyrodite sulfide-based solid electrolyte Li6 PS5 Cl (LPSC) is considered to have great potential in solid-state battery applications due to its ion conductivity being comparable to that of liquid electrolytes. However, interfacial instability between LPSC and Li during cycling, resulting in battery polarization, is an ongoing problem. Here, we report that CO2 adsorption can play a crucial role in improving both interfacial and electrochemical stability between lithium and LPSC. Investigating the formation of the new S–CO2 bond, examined here using various analytical techniques, is pivotal to modifying interfacial behavior. It enhances the interfacial stability between lithium and LPSC and reduces cell resistance. Moreover, the Li|CO2 @LPSC|LTO shows an amazing result, with 62% capacity retention and ultra-high coulombic efficiency of 99.91% after 1000 cycles. Interestingly, the same concept was also applied to the high ionic conductivity sulfide-based superionic conductor Li10 GeP2 S12 (LGPS) system, which also has the PS4 3− moiety. It also enhanced the stability at the lithium and LGPS interface. This work offers a new direction toward reducing the interfacial resistance of sulfide-based solid electrolytes; it increases the possibility of realizing sulfide-based all-solid-state lithium metal batteries.